How does immigration affect housing costs in Switzerland? - Fabienne Helfer; Volker Grossmann; Aderonke Osikominu (Swiss Journal of Economics and Statistics, 2023)
Abstract This paper examines the short-run immigration effects on prices for owner-occupied housing and rents in Switzerland, exploiting regional variation at the level of 106 local labor markets (“Mobilité Spatiale” regions) and 26 cantons, respectively. We propose two empirical strategies that exploit the Agreement on the Free Movement of Persons (AFMP) with the European Union (EU), enacted in 2002, as an exogenous shock to immigration. The first approach uses the AFMP reform within an instrumental variable approach, instrumenting current regional inflows of immigrants based on the historical distribution of immigrants across regions. The second conducts an event study of housing price changes before and after the reform, distinguishing between regions with historically high, medium, and low immigration from EU-15 countries. The analysis based on data at the level of local labor markets for the years 1985–2016 suggests that immigration triggered off by the AFMP reform has substantially raised prices of single-family homes and of owner-occupied apartments. Before the reform, immigration has not affected house prices. Estimates based on cantonal data for the years 1998–2016 suggest that immigration has raised rental prices even more than prices of owner-occupied housing.